KEBIJAKAN RUANG PUBLIK PEREMPUAN DI SAUDI ARABIA: Benarkah Sebuah Agenda Politik Double Interest? - Roji, Fatkhur (International Journal Ihya' 'Ulum al-Din, 2017)
The emergence of the Saudi government's policy of allowing women to drive alone these days has become an interesting phenomenon to be examined, since before they forbid women to drive without a mahram. Since the appointment of the crown prince Salman bin Abdul Aziz, the Saudi government appears more dynamic and moderate. This new policy is in place to promote the development of the country with and to give women the right to participate freely in it. Observers see this as a political agenda of government, where with the political interest is expected Saudi Arabia can compete in the increasingly tight global economic competition. This article examines the policies of the Saudi Arabian government thoroughly from a social, economic, and political standpoint.Munculnya kebijakan pemerintahan Saudi Arabia yang membolehkan perempuan untuk berkendara sendiri akhir-akhir ini menjadi fenomena yang menarik untuk diteliti, sebab sebelumnya mereka melarang perempuan berkendara tanpa mahram. Semenjak diangkatnya putera mahkota Salman bin Abdul Aziz, pemerintahan Saudi tampil lebih dinamis dan moderat. Kebijakan baru ini diberlakukan untuk meningkatkan perkembangan negara dengan dan untuk memberikan hak terhadap perempuan agar dapat berperan bebas di dalamnya. Para pengamat melihat ini sebagai agenda politik pemerintahan, dimana dengan kepentingan politik tersebut diharapkan Saudi Arabia dapat ikut bersaing dalam kompetisi ekonomi global yang semakin ketat. Artikel ini mengamati kebijakan pemerintah Saudi Arabia ini secara menyeluruh dari sudut pandang sosial, ekonomi, dan politik.